Anti-dazzle anti-reflection anti-fingerprint film
By using a combination of transparent support, anti-glare hardening coating and anti-reflective coating in anti-glare, anti-reflective and anti-fingerprint films, combined with UV curing and heat crosslinking technology, the adhesion and wear resistance of existing films are solved. The problem of insufficient sexuality achieves better anti-glare, low reflection and anti-fingerprint effects.
Patent Information
- Application Number
- CN202411834296.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-21
AI Technical Summary
The existing anti-glare, anti-reflection and anti-fingerprint films have adhesion problems, poor friction resistance and insufficient durability during the production process.
An anti-glare anti-reflective anti-fingerprint film including a transparent support, an anti-glare hardening coating and an anti-reflective coating is used. The anti-glare hardening coating consists of resin, photoinitiator, thermal curing agent, anti-glare particles and leveling agent. The anti-reflective coating uses modified hollow silica nanoparticles and thermal curing resin to be used to cure and thermally cross-link. Technology enhances adhesion and wear resistance.
The comprehensive effect of anti-glare, low reflection and anti-fingerprint is achieved, while improving the adhesion and friction resistance of the coating, solving the persistence and wear resistance problems in the prior art.
Smart Images

Figure BDA0005188079610000121 
Figure BDA0005188079610000201 
Figure BDA0005188079610000211
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thin films and relates to an anti-glare, anti-reflection and anti-fingerprint film. Background Art
[0002] With the popularization of tools such as cars, mobile phones, and laptops, display screens are developing towards larger screens and higher definition, and consumers are increasingly demanding display screens, pursuing a better experience. Functional films with anti-glare, anti-reflection, and anti-fingerprint properties (i.e., 3A films) are increasingly favored by consumers and valued by manufacturers.
[0003] The anti-glare, anti-reflection and anti-fingerprint functional film (i.e. 3A film) pasted on the display panel can provide basic protection for the display device, achieving anti-glare effect while reducing or eliminating surface reflected light; it can provide clearer display effect and improve the driver's visual experience and safety.
[0004] Currently, the wet coating production method can reduce production costs and improve production efficiency, but wet coating also faces problems such as adhesion between the anti-glare layer and the anti-reflective coating, and the durability of the anti-reflective coating's friction resistance and anti-fingerprint. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides an anti-glare, anti-reflection and anti-fingerprint film, which has anti-glare and low reflection properties as well as good anti-fingerprint performance, coating adhesion, and friction resistance.
[0006] In order to achieve the above technical objectives, the technical solution adopted by the present application is an anti-glare, anti-reflection and anti-fingerprint film, comprising a transparent support, an anti-glare hardened coating and an anti-reflection coating; the anti-glare hardened coating is obtained by coating and curing a coating liquid made of the following components in parts by mass:
[0007] Resin 1: 20-40 parts
[0008] Resin 2: 1.8-4.8 parts
[0009] Photoinitiator: 0.75-3.25 parts
[0010] Thermal curing agent: 0.3-1.75 parts
[0011] Anti-glare particles: 0.75-4.75 parts
[0012] Leveling agent 1: 0.25-1.25 parts
[0013] Leveling agent 2: 0.03-0.15 parts
[0014] Solvent: 44.05-76.12 parts;
[0015] The anti-reflection coating is formed by coating and curing a coating solution made of the following components in parts by mass:
[0016] Resin 2: 0.47-1.8 parts
[0017] Resin 3: 2.4-6.0 parts
[0018] Photoinitiator: 0.12-0.75 parts
[0019] Thermal curing agent: 0.1-0.45 parts
[0020] Leveling agent 3: 0.18-1.65 parts
[0021] Modified hollow silica: 0.56-2.4 parts
[0022] Wetting and dispersing agent: 0.1-1.25 parts
[0023] Solvent: 85.7-95.74 parts;
[0024] The modified hollow silica is a three-layer structured hollow silica nanoparticle formed by compounding polydimethylsiloxane (PDMS) on the surface of the hollow silica nanoparticle and then surface-modifying the hollow silica nanoparticle with 3-glycidyloxypropyltrimethoxysilane (GPTMS).
[0025] Furthermore, the anti-glare particles contained in the anti-glare hardening coating are monodisperse particles, and their particle size D1 and the anti-glare hardening coating thickness H1 satisfy the following relationship: H1≤D1≤5 / 4H1, 1.5um≤H1≤4um; the modified hollow silica nanoparticles, the particle size D2 and the anti-reflection coating thickness H2 satisfy: 90nm≤H2≤150nm, D2<90nm.
[0026] Further, the anti-glare hardening coating comprises resin 1 and resin 2; the resin 1 is polyurethane acrylic resin, the curing method thereof is UV energy curing, the functionality is 6-9, and the molecular weight is 1000-8000; the resin 2 is polyol acrylate, the curing method is thermal cross-linking curing, the hydroxyl value is 85-120, the thermal curing conditions are 80-100°C, 5-10min, the curing temperature is 60°C, and the curing time is ≥12h;
[0027] The mass of the resin 2 in the anti-glare hardened coating is not higher than 12% of the mass of the resin 1.
[0028] Furthermore, resin 2 and resin 3 are used in the anti-reflection coating;
[0029] The resin 3 is a low-refractive modified polyurethane acrylic resin, which is cured by UV energy and has a refractive index of 1.35±0.1;
[0030] The mass of resin 2 in the anti-reflection coating is not higher than 30% of the mass of resin 3.
[0031] Furthermore, the leveling agent 1 is an acrylic leveling agent, and the leveling agents 2 and 3 are silicone leveling agents.
[0032] Furthermore, the solvent used in the anti-glare hardening coating liquid is a mixed solvent of n-propanol, butyl acetate and butanone, and the mixed solubility parameter of the mixed solvent is 9 to 11;
[0033] The solvent used in the anti-reflection coating liquid is a mixed solvent of ethyl acetate and methyl isobutyl ketone, and the mixed solubility parameter of the mixed solvent is 7-10.
[0034] Furthermore, the transparent support is one of TAC, PET, SRF, PMMA or PI.
[0035] Furthermore, the transparent support has a thickness of 40-125 μm.
[0036] Beneficial Effects
[0037] 1. The anti-glare, anti-reflection and anti-fingerprint film of the present invention has an anti-reflection layer in which low-refractive nanoparticles are hollow composite nanoparticles PDME-SiO2 with surface modified by 3-glycidyloxypropyltrimethoxysilane. The surface modification by 3-glycidyloxypropyltrimethoxysilane can connect the composite nanoparticles with covalent bonds, and the particles are relatively stable. The composite structure of hollow SiO2 coated with PDME can provide a lower refractive index, effectively reduce reflected light, and enhance the compatibility of the nanoparticles in the resin. In addition, PDME has a lower surface energy, can provide certain anti-fouling performance, and can reduce the sedimentation of the composite nanoparticles in the coating liquid, so that the composite nanoparticles are stably distributed in the coating liquid, and due to the effect of the covalent bonds, the nanoparticles are firmly anchored in the anti-reflection coating.
[0038] 2. The anti-glare, anti-reflection and anti-fingerprint film of the present invention uses UV curing resin and thermal curing resin for its anti-glare layer. After the anti-glare layer and the anti-reflection layer are successively UV cured, the UV cured coating is thermally cured, which helps to cause thermal cross-linking between the anti-reflection layer and the anti-glare layer, strengthens the connection force between the coatings, and enhances adhesion.
[0039] 3. The anti-glare, anti-reflection and anti-fingerprint film of the present invention has the following relationship between the thickness of the anti-glare coating and the particle size of the anti-glare particles: the particle size (D1) of the anti-glare particles in the anti-glare coating and the thickness (H1) of the anti-glare hardened coating satisfy H1≤D1≤5 / 4H1, 1.5um≤H1≤4um; the particle size D2 of the modified hollow silica nanoparticles and the thickness H2 of the anti-reflection coating satisfy: 90nm≤H2≤150nm, D2<90nm. Controlling the relationship between the particle size and the coating thickness of the anti-glare particles in the anti-glare coating, on the one hand, ensures that the anti-glare particles form a protruding structure, provides a certain surface roughness, and achieves an anti-glare effect; on the other hand, limiting the protruding height of the particle size, avoiding too high, while ensuring the uniformity of the protruding structure, can provide a relatively uniform coating surface with appropriate roughness for the nano-sized anti-reflection coating, further ensure the thickness uniformity of the anti-reflection coating, and achieve a better anti-reflection effect.
[0040] In summary, the anti-glare hardening coating strictly requires the anti-glare particles and coating thickness conditions, and uses UV curing resin and thermal curing resin at the same time; the anti-reflection coating also uses thermal curing resin and low-refractive UV curing resin, and the hollow silica nanoparticles are polymer-coated and surface-modified, anchored in the resin, and provide a low surface energy nano coating for a long time. The above technical means can make it have anti-glare and low reflection properties, as well as good anti-fingerprint performance, coating adhesion, and friction resistance. DETAILED DESCRIPTION
[0041] In order to solve the existing problems of anti-glare, anti-reflection and anti-fingerprint films, the anti-glare, anti-reflection and anti-fingerprint film of the present invention is obtained by coating a layer of anti-glare hardening coating on one side of a support body, and coating a layer of nano anti-reflection coating on the surface of the anti-glare hardening coating; and by controlling the coating thickness, particle size, nano modification and reasonable use of thermal curing resin and UV curing resin, the anti-glare, anti-reflection and anti-fingerprint film with good anti-glare and low reflection effects can be obtained, which also has good anti-fingerprint performance, coating adhesion and friction resistance.
[0042] An anti-glare, anti-reflection and anti-fingerprint film comprises a transparent support, an anti-glare hardening coating and an anti-reflection coating.
[0043] The transparent support is one of TAC, PET, SRF, PMMA or PI, and the thickness of the transparent support is 40-125 μm.
[0044] The anti-glare hardening coating contains anti-glare particles, the anti-glare particles are monodisperse particles, and their particle size D1 and the thickness H1 of the anti-glare hardening coating satisfy the following relationship: H1≤D1≤5 / 4H1, 1.5um≤H1≤4um; the relationship between the particle size of the anti-glare particles in the anti-glare hardening coating and the coating thickness is controlled. On the one hand, it is ensured that the anti-glare particles form a protruding structure, provide a certain surface roughness, and achieve an anti-glare effect; on the other hand, the protruding height of the particle size is limited to avoid being too high, while ensuring the uniformity of the protruding structure, which can provide a relatively uniform coating surface with suitable roughness for the nano-sized anti-reflection coating, further ensure the thickness uniformity of the anti-reflection coating, and achieve a better anti-reflection effect. The anti-glare particles used in the anti-glare hardening coating of the present invention have a particle size of 1.5-5 μm, and can be BM30X-5 (monodisperse PBMA 5 μm), SSX-103 (monodisperse PMMA 3 μm), SSX-104 (monodisperse MMA 4 μm), MB-4 (monodisperse PMMA 4 μm) produced by Sekisui Chemical Co., Ltd.; MX-180TA (monodisperse PMMA 1.8 μm) produced by Soken Chemical Co., Ltd.
[0045] In some embodiments, the anti-glare hardening coating includes resin 1 and resin 2.
[0046] The resin 1 is a polyurethane acrylic resin, which is cured by UV energy curing, has a functionality of 6-9, and a molecular weight of 1000-8000. The resin 1 (UV curing resin) used in the anti-glare hardening coating is polyurethane, acrylate, epoxy resin, etc., preferably 6-9 functional polyurethane acrylate, such as Sartomer CN 997, Cytec EB 2220, EB 5129, Changxing 6145-100.
[0047] The resin 2 is polyol acrylate, the curing method is thermal crosslinking curing, the hydroxyl value is 85-120, the thermal curing conditions are 80-100°C, 5-10min, and the aging temperature is 60°C, ≥12h. Resin 2 (thermosetting resin) can be hydroxyl-terminated polyurethane and acrylate, etc., preferably a polyurethane with a molecular weight of 1000-6000, such as DIC Corporation PANDEX P-910, OD-X-2195, etc.
[0048] In some embodiments, the anti-reflection coating contains modified hollow silica nanoparticles, and the particle size D2 and the thickness H2 of the anti-reflection coating satisfy: 90nm≤H2≤150nm, D2<90nm.
[0049] Resin 2 and resin 3 are used in the anti-reflection coating. Resin 3 is a low-refractive modified polyurethane acrylic resin, which is cured by UV energy curing and has a refractive index of about 1.40. Specifically, the anti-reflection coating uses resin 3 (UV-cured low-refractive resin), and a fluorine-free low-refractive polyurethane acrylic resin is selected, such as sapience SPC-1410 (refractive index 1.4) and Qiaorun New Material JR7207 (refractive index 1.35).
[0050] The anti-glare hardening coating and the anti-reflection coating of the present invention both use thermal curing and UV curing resins. The anti-glare hardening coating is cured by UV energy (UV curing energy is 450mJ / cm 2 ~780mJ / cm 2 ) After the initial curing, a layer of anti-reflection coating is coated on its surface; after UV curing (UV curing energy is 450mJ / cm2~780mJ / cm2), thermal curing (curing conditions are 90-110℃, 2-5min) and aging (aging conditions are 60℃, 36h). On the one hand, after the anti-glare hardening coating is UV cured, the thermal curing resin is not cured, which can provide a large surface energy for anti-reflection and spread the particle anti-reflection layer; on the other hand, after thermal curing and subsequent aging process, the thermal curing resin in the anti-reflection layer and the anti-glare layer are cross-linked at the interface of the two coatings, which strengthens the connection between the two coatings and provides a strong adhesion between the anti-glare hardening coating and the anti-reflection layer.
[0051] In some embodiments, the mass of resin 2 in the anti-glare hardening coating is not higher than 12% of the mass of resin 1. An appropriate proportion of resin 2 (thermosetting resin) can provide a higher surface energy after UV curing of the anti-glare hardening coating, while ensuring physical properties such as hardness and wear resistance. The mass of resin 2 in the anti-reflection coating is not higher than 30% of the mass of resin 3. Adding a certain proportion of thermosetting resin to the anti-reflection coating can cross-link with the uncured thermosetting resin in the anti-glare coating to enhance the adhesion between the coatings and other physical properties; however, too high a proportion will increase the refractive index of the coating, affect the anti-reflection effect, and at the same time weaken the physical properties such as hardness.
[0052] In some embodiments, the anti-glare hardened coating is obtained by coating and curing a coating solution made of the following components in parts by weight:
[0053] Resin 1: 20-40 parts
[0054] Resin 2: 1.8-4.8 parts
[0055] Photoinitiator: 0.75-3.25 parts
[0056] Thermal curing agent: 0.3-1.75 parts
[0057] Anti-glare particles: 0.75-4.75 parts
[0058] Leveling agent 1: 0.25-1.25 parts
[0059] Leveling agent 2: 0.03-0.15 parts
[0060] Solvent: 44.05-76.12 parts;
[0061] The solvent used is a mixed solvent of n-propanol, butyl acetate and butanone, and the mixed solubility parameter of the mixed solvent is 9-11.
[0062] The anti-reflection coating is obtained by coating and curing a coating solution made of the following components in parts by mass:
[0063] Resin 2: 0.47-1.8 parts
[0064] Resin 3: 2.4-6.0 parts
[0065] Photoinitiator: 0.12-0.75 parts
[0066] Thermal curing agent: 0.1-0.45 parts
[0067] Leveling agent 3: 0.18-1.65 parts
[0068] Modified hollow silica: 0.56-2.4 parts
[0069] Wetting and dispersing agent: 0.1-1.25 parts
[0070] Solvent: 85.7-95.74 parts;
[0071] The solvent is a mixed solvent of ethyl acetate and methyl isobutyl ketone, and the mixed solubility parameter of the mixed solvent is 7-10.
[0072] The modified silica nanoparticles are hollow SiO2 nanoparticles with a three-layer structure, that is, hollow SiO2 is composited with PDMS and then modified with 3-glycidyloxypropyltrimethoxysilane (GPTMS) to obtain GPTMS-PDME-SiO2 composite nanoparticles with a hollow structure.
[0073] The modified silica nanoparticles added to the anti-reflection coating of the present invention are coated with a layer of nano-scale PDMS polymer on the surface and modified by a surfactant; they have the characteristics of low refractive index, low surface energy, and particles connected by covalent bonds, which can effectively reduce the refractive index of the coating and provide a certain degree of anti-fingerprint effect; at the same time, the modified silica nanoparticles are stably and evenly dispersed to effectively prevent agglomeration.
[0074] The modified silicon dioxide nanoparticle preparation method is as follows:
[0075] Step 1: Preparation of hollow composite nanoparticles PDMS-SiO2: In air at room temperature, under magnetic stirring, slowly add hollow SiO2 nanoparticles into a round-bottom flask containing a mixed solution of butyl acetate and nitrogen methyl pyrrolidone; after ultrasonication for 10 minutes, add an appropriate amount of nanoparticle dispersant and continue stirring for 15 minutes. Then, add an appropriate amount of dihydroxy polydimethylsiloxane (HO-PDMS-OH) and triethoxymethylsilane (MeTEOS) to the flask successively, and stir for 10 minutes until the mixed system is uniform. Heat the flask to 60°C, add the catalyst, continue mixing and stirring under condensation reflux conditions for 120 minutes, and obtain hollow composite nanoparticles PDMS-SiO2 by high-speed centrifugation. Wash PDMS-SiO2 with ethanol 3 times, and finally dry it to obtain dry hollow composite nanoparticles PDMS-SiO2.
[0076] Step 2: Add the PDMS-SiO2 nanoparticles and toluene prepared in the first step to a round-bottom flask; stir continuously at room temperature for 5 minutes, and then ultrasonicate for 10 minutes; continue stirring, and under stirring, add 3-glycidyloxypropyltrimethoxysilane (GPTMS) dropwise to the mixture, keep stirring constantly for 24 hours; obtain 3-glycidyloxypropyltrimethoxysilane-modified GPTMS-PDME-SiO2 by high-speed centrifugation. Wash the GPTMS-PDME-SiO2 with ethanol three times, and finally dry it to obtain dry GPTMS-PDME-SiO2 nanopowder.
[0077] The photoinitiator used in the anti-glare hardening coating and the anti-reflective coating (low-reflective coating liquid coating) of the present invention is one of a free radical polymerization photoinitiator and a cationic polymerization photoinitiator, such as benzoin and its derivatives, alkyl iodonium salts, etc., for deep photocuring of the coating, and BASF Irgacure TPO, Lencolo 5020, and IGM Omnirad819 can be selected.
[0078] The heat curing agent used in the anti-glare hardening coating and the anti-reflection coating of the present invention is an isocyanate curing agent, and Basonat HI100ap and Basonat HB175 of BASF, or Desmodur Z4470 MPA / X of Covestro can be selected.
[0079] The leveling agent 1 in the anti-glare hardening coating of the present invention is an acrylic leveling agent, and Guangdong Jiaming CM-703, CM-6358N and BYK Chemical BYK-358N, BYK-371 can be selected.
[0080] The leveling agent 2 in the anti-glare hardening coating of the present invention is a silicone leveling agent, and Guangdong Jiaming CM-306, BASF SL 3239.
[0081] The leveling agent 3 of the anti-reflective coating in the present invention is a modified silicone leveling agent, which can significantly reduce the surface energy of the coating while performing the leveling effect on the coating. STA-3306, BYK-3700, and LAG-606 can be selected.
[0082] The wetting dispersant of the anti-reflective coating in the present invention can be a polyurethane dispersant, such as BYK DISPERBYK-170TF, DISPERBYK-174; or an acrylic dispersant, such as BYK DISPERBYK-2026, DISPERBYK-2025, which can have good dispersibility for the prepared modified hollow silica. The present invention is further described below in conjunction with the embodiments.
[0083] Examples of anti-glare hard coating:
[0084] Example 1
[0085] CN 997: 20g
[0086] OD-X-2195: 1.8g
[0087] Lencolo 5020: 0.75g
[0088] BasonatHI100ap: 0.3g
[0089] SSX-104: 0.75g
[0090] CM-703: 0.25g
[0091] CM-306: 0.03g
[0092] Mixed solvent: 76.12g;
[0093] 20 g of polyurethane acrylate resin (Sartomer CN 997), 1.8 g of polyurethane (DIC Corporation OD-X-2195), 0.75 g of photoinitiator (Lencolo 5020), 0.3 g of thermal curing agent (BASF Basonat HI100ap), 0.75 g of anti-glare particles (Sekisui Chemical Co., Ltd. SSX-104, monodisperse MMA 4 μm), 0.25 g of acrylic leveling agent (Guangdong Jiaming CM-703), 0.03 g of silicone leveling agent (Guangdong Jiaming CM-306) and 76.12 g of a mixed solvent of n-propanol, butyl acetate and butanone in a mass ratio of 1:2:1 were poured into a beaker, first stirred at a low speed of 300 rpm for 10 min, then stirred at a high speed of 1000 rpm for 60 min, and stirred evenly to obtain a coating solution.
[0094] The coating liquid was evenly scraped onto the surface of the 80 um SRF substrate using a wire rod coating method, and after being treated in an oven at 55° C. for 3 minutes, it was cured by ultraviolet light to obtain an anti-glare hardened coating.
[0095] Example 2
[0096] Sartomer CN 997: 20g
[0097] DIC Co., Ltd. OD-X-2195: 2.4g
[0098] Lencolo 5020: 1.625g
[0099] Desmodur Z4470 MPA / X: 0.875g
[0100] SSX-104: 2.3g
[0101] Guangdong Jiaming CM-703: 1.25g
[0102] Guangdong Jiaming CM-306: 0.15g
[0103] Mixed solvent: 71.4 g;
[0104] The coating liquid configuration process and method are the same as those in Example 1, and the coating method and curing method are also as described in Example 1 to obtain an anti-glare hardened coating.
[0105] Example 3
[0106] EB 2220: 40g
[0107] PANDEX P-910: 4.8g
[0108] IGM Omnirad 819: 3.25g
[0109] Desmodur Z4470 MPA / X: 1.75g
[0110] SSX-103: 4.75g
[0111] BYK-358N: 1.25g
[0112] SL 3239: 0.15g
[0113] Mixed solvent: 44.05g;
[0114] The coating liquid configuration process and method are the same as those in Example 1, and the coating method and curing method are also as described in Example 1 to obtain an anti-glare hardened coating.
[0115] Example 4
[0116] EB 2220:35
[0117] PANDEX P-910: 4.2g
[0118] IGM Omnirad 819: 2.5g
[0119] Desmodur Z4470 MPA / X: 1.2g
[0120] SSX-103: 4.1g
[0121] BYK-358N: 1.0g
[0122] SL 3239: 0.08g
[0123] Mixed solvent: 51.92g;
[0124] The coating liquid configuration process and method are the same as those in Example 1, and the coating method and curing method are also as described in Example 1 to obtain an anti-glare hardened coating.
[0125] Example 5
[0126] EB 2220: 30g
[0127] PANDEX P-910: 2.4g
[0128] IGM Omnirad 819: 2.25g
[0129] Desmodur Z4470 MPA / X: 0.5
[0130] SSX-103: 3.4g
[0131] BYK-358N: 1g
[0132] SL 3239: 0.08g
[0133] Mixed solvent: 60.37 g;
[0134] The coating liquid configuration process and method are the same as those in Example 1, and the coating method and curing method are also as described in Example 1 to obtain an anti-glare hardened coating.
[0135] Comparative Example 1
[0136] EB 2220: 32.4g
[0137] PANDEX P-910: 0g
[0138] IGM Omnirad 819: 2.25g
[0139] Desmodur Z4470 MPA / X: 0.5g
[0140] SSX-103: 3.4g
[0141] BYK-358N: 1.0g
[0142] SL 3239: 0.08g
[0143] Mixed solvent: 60.37 g;
[0144] The coating liquid preparation process and method are the same as those in Example 1. The coating liquid is evenly scraped onto the surface of the 80um SRF substrate using a wire rod coating method. After being treated in an oven at 55°C for 3 minutes, it is cured by ultraviolet light to obtain an anti-glare hardened coating.
[0145] Comparative Example 2
[0146] EB 2220: 28.17g
[0147] PANDEX P-910: 4.23g
[0148] IGM Omnirad 819: 2.25g
[0149] Desmodur Z4470 MPA / X: 0.5g
[0150] SSX-103: 3.4g
[0151] BYK-358N: 1.0g
[0152] SL 3239: 0.08g
[0153] Mixed solvent: 60.37 g;
[0154] The coating liquid preparation process and method are the same as those in Example 1. The coating liquid is evenly scraped onto the surface of the 80um SRF substrate using a wire rod coating method. After being treated in an oven at 55°C for 3 minutes, it is cured by ultraviolet light to obtain an anti-glare hardened coating.
[0155] Comparative Example 3
[0156] EB 2220: 30g
[0157] PANDEX P-910: 2.4g
[0158] IGM Omnirad 819: 2.25g
[0159] Desmodur Z4470 MPA / X: 0.5
[0160] SSX-108: 3.4g
[0161] BYK-358N: 1g
[0162] SL 3239: 0.08g
[0163] Mixed solvent: 60.37 g;
[0164] The coating liquid preparation process and method are the same as those in Example 1. The coating liquid is evenly scraped onto the surface of the 80um SRF substrate using a wire rod coating method. After being treated in an oven at 55°C for 3 minutes, it is cured by ultraviolet light to obtain an anti-glare hardened coating.
[0165] The above-mentioned Examples 1-4 and Comparative Examples 1-3 were subjected to performance tests, and the results are shown in Table 1:
[0166] Table 1 Performance test of anti-glare hardening coating
[0167]
[0168] According to the test data of Examples 1-5, it can be seen that the proportion of resin in the formula, the proportion of thermosetting resin, etc. have a significant impact on the total haze, external haze, roughness, water drop angle, etc. Compared with the test results of Comparative Examples 1 and 2 of Example 5, it can be seen that when the amount of thermosetting resin added is 0, the water drop angle is significantly improved relative to Example 5, indicating that a certain proportion of thermosetting resin can improve the surface energy; however, when the amount of thermosetting resin added is increased to 15%, the surface hardness and wear resistance are significantly reduced. Compared with the test results of Comparative Example 3 of Example 5, it can be seen that when the particle size and coating thickness do not meet H1≤D1≤5 / 4H1, 1.5um≤H1≤4um, the roughness will change significantly. Here, large-size particles are used, the roughness is significantly improved, and the water drop angle is also improved, which is not conducive to re-coating the anti-reflection layer on the surface.
[0169] According to the test results of the above embodiments and comparative examples, the test data results of embodiment 5 are haze 7.15%, surface roughness 0.18 μm, and water drop angle 70.5°. The surface of the anti-glare hardened coating prepared in embodiment 5 is further coated with a low-reflection coating. The specific embodiments are as follows:
[0170] Example 6
[0171] PANDEX P-910: 0.8g
[0172] Sapience SPC-1410: 2.4g
[0173] IGM Omnirad 819: 0.12g
[0174] BasonatHI100ap: 0.1g
[0175] LAG-606: 0.18g
[0176] Modified hollow silica: 0.56g
[0177] BYK DISPERBYK-170TF: 0.1g
[0178] Mixed solvent: 95.74g;
[0179] 0.8 g of polyurethane (DIC Corporation PANDEX P-910), 2.4 g of silicon-modified polyurethane acrylate resin low-fold resin (sapience SPC-1410), 0.12 g of photoinitiator (IGM Omnirad 819), 0.1 g of thermal curing agent (BASF Basonat HI100ap), 0.18 g of organic silicone leveling agent (LAG-606) and 65.74 g of a mixed solvent of ethyl acetate and methyl isobutyl ketone in a mass ratio of 1:1 were poured into a beaker, and stirred at a low speed of 300 rpm for 10 min to mix the resin system evenly;
[0180] 0.56g of the prepared hollow nano-silica with a three-layer structure was dissolved in 30g of a mixed solvent (a mixed solvent of ethyl acetate and methyl isobutyl ketone in a mass ratio of 1:1), and magnetically stirred at 400rpm for 10min. After being uniform, 0.1g of a wetting dispersant (purchased from BYK DISPERBYK-170TF) was added, and then stirred at 500rpm for 20min to obtain a uniformly mixed suspension of hollow silica. The speed was reduced to 200rpm, and the above-mentioned uniformly stirred resin system was slowly added to the stirring suspension of hollow silica, and the magnetic stirring speed was increased to 500rpm, and stirring was continued for 30min to obtain a low-reflection coating liquid. Finally, the speed was adjusted to 200rpm, and the surface was defoamed after stirring at a low speed before use.
[0181] The specific preparation method of hollow nano-silica with a three-layer structure is as follows:
[0182] Step 1: Preparation of hollow composite nanoparticles PDMS-SiO2: In air at room temperature, under magnetic stirring, slowly add 2.0g of hollow SiO2 nanoparticles (purchased from Acros reagent, particle size 70-80nm) into a round-bottom flask containing 60g of butyl acetate (purchased from Gaide Chemical, analytical grade) and 80g of nitrogen methyl pyrrolidone (purchased from Gaide Chemical, analytical grade) mixed solvent, after ultrasonication for 10 minutes, add 0.75g of BYK-103 nanoparticle dispersant (purchased from BYK Chemical), and continue stirring for 15 minutes. Then, 0.12g of dihydroxy polydimethylsiloxane (HO-PDMS-OH) (purchased from Sigma-Aldrich) and 0.07g of triethoxymethylsilane (MeTEOS) (purchased from Sigma-Aldrich) are added to the flask successively, and stirred for 10 minutes until the mixed system is uniform. The flask was heated to 60°C, and a catalyst dibutyltin diacetate (purchased from Aladdin Reagent) was added, and mixing and stirring were continued for 120 minutes under condensation reflux conditions. Hollow composite nanoparticles PDMS-SiO2 were obtained by high-speed centrifugation. The PDMS-SiO2 was washed with ethanol for 3 times, and finally dried to obtain dry hollow composite nanoparticles PDMS-SiO2.
[0183] Step 2: Add 1.8g of the PDMS-SiO2 nanoparticles prepared in the first step and 70g of toluene to a round-bottom flask and stir continuously at room temperature for 5 minutes; after ultrasonic treatment for 10 minutes, continue stirring, and under stirring, add 1.0g of 3-glycidyloxypropyltrimethoxysilane (GPTMS) dropwise to the mixture, keep stirring constantly for 24 hours; obtain 3-glycidyloxypropyltrimethoxysilane-modified GPTMS-PDME-SiO2 by high-speed centrifugation. Wash the GPTMS-PDME-SiO2 with ethanol three times, and finally dry it at 80°C in vacuum for 12 hours to obtain dry GPTMS-PDME-SiO2 nanopowder.
[0184] The low-reflection coating liquid prepared above was evenly scraped onto the surface of Example 6 by a wire rod coating method, treated in an oven at 85°C for 7 minutes, then cured by ultraviolet light, and then aged at 60°C for 24 hours to obtain the anti-glare, anti-reflection, and anti-fingerprint film.
[0185] Example 7
[0186] PANDEX P-910: 1.2g
[0187] Sapience SPC-1410: 3.2g
[0188] Irgacure TPO: 0.16g
[0189] BasonatHI100ap: 0.15g
[0190] STA-3306: 0.35g
[0191] Modified hollow silica: 1.0g
[0192] BYK DISPERBYK-170TF: 0.5g
[0193] Mixed solvent: 93.44 g;
[0194] 1.2 g of polyurethane (DIC Corporation PANDEX P-910), 3.2 g of silicon-modified polyurethane acrylate resin low-fold resin (sapience SPC-1410), 0.16 g of photoinitiator (BASF Irgacure TPO), 0.15 g of thermal curing agent (BASF Basonat HI100ap), 0.35 g of organic silicone leveling agent (STA-3306) and 55.94 g of a mixed solvent of ethyl acetate and methyl isobutyl ketone in a mass ratio of 1:1 were poured into a beaker, and stirred at a low speed of 300 rpm for 10 min to mix the resin system evenly;
[0195] 1.0g of the prepared three-layer hollow nano-silica was dissolved in 37.5g of mixed solvent, and magnetically stirred at 400rpm for 10min. After being uniform, 0.5g of wetting dispersant (purchased from BYK DISPERBYK-170TF) was added, and then stirred at 500rpm for 20min to obtain a uniformly mixed suspension of hollow silica. The speed was reduced to 200rpm, and the above-mentioned uniformly stirred resin system was slowly added to the stirring suspension of hollow silica, and the magnetic stirring speed was increased to 500rpm, and stirring was continued for 30min to obtain a low-reflection coating liquid. Finally, the speed was adjusted to 200rpm, and the surface was defoamed after low-speed stirring before use.
[0196] The steps for preparing the three-layer structure of hollow nano-silica are as described in Example 7. The coating method and curing method are as described in Example 7 to obtain the anti-glare, anti-reflection and anti-fingerprint film.
[0197] Example 8
[0198] PANDEX P-910: 1.2g
[0199] Sapience SPC-1410: 4.0g
[0200] Irgacure TPO: 0.16g
[0201] Desmodur Z4470 MPA / X: 0.15g
[0202] LAG-606: 0.35g
[0203] Modified hollow silica: 1.56g
[0204] DISPERBYK-2026: 0.81g
[0205] Mixed solvent: 91.77g;
[0206] 1.2 g of polyurethane (DIC Corporation PANDEX P-910), 4.0 g of silicon-modified polyurethane acrylate resin low-fold resin (sapience SPC-1410), 0.16 g of photoinitiator (BASF Irgacure TPO), 0.15 g of thermal curing agent (Covestro Desmodur Z4470 MPA / X), 0.35 g of silicone leveling agent (LAG-606) and 43.02 g of a mixed solvent of ethyl acetate and methyl isobutyl ketone in a mass ratio of 1:1 were poured into a beaker and stirred at a low speed of 300 rpm for 10 minutes to mix the resin system evenly.
[0207] 1.56g of the prepared three-layer hollow nano-silica was dissolved in 48.75g of the mixed solvent, and magnetically stirred at 400rpm for 10min. After being uniform, 0.81g of wetting dispersant (purchased from BYK Chemical DISPERBYK-2026) was added, and then stirred at 500rpm for 20min to obtain a uniformly mixed suspension of hollow silica. The speed was reduced to 200rpm, and the above-mentioned uniformly stirred resin system was slowly added to the stirring suspension of hollow silica, and the magnetic stirring speed was increased to 500rpm, and stirring was continued for 30min to obtain a low-reflection coating liquid. Finally, the speed was adjusted to 200rpm, and the surface was defoamed after low-speed stirring before use.
[0208] The steps for preparing the three-layer structure of hollow nano-silica are as described in Example 7. The coating method and curing method are as described in Example 7 to obtain the anti-glare, anti-reflection and anti-fingerprint film.
[0209] Example 9
[0210] PANDEX P-910: 1.8g
[0211] Sapience SPC-1410: 6.0g
[0212] IGM Omnirad 819: 0.75g
[0213] Desmodur Z4470 MPA / X: 0.45g
[0214] STA-3306: 1.65g
[0215] Modified hollow silica: 2.4g
[0216] DISPERBYK-2026: 1.25g
[0217] Mixed solvent: 85.7 g;
[0218] 1.8 g of polyurethane (DIC Corporation PANDEX P-910), 6.0 g of silicon-modified polyurethane acrylate resin low-fold resin (sapience SPC-1410), 0.75 g of photoinitiator (IGM Omnirad 819), 0.45 g of thermal curing agent (Covestro Desmodur Z4470 MPA / X), 1.65 g of silicone leveling agent (STA-3306) and 85.7 g of a mixed solvent of ethyl acetate and methyl isobutyl ketone in a mass ratio of 1:1 were poured into a beaker and stirred at a low speed of 300 rpm for 10 minutes to mix the resin system evenly.
[0219] 2.4g of the prepared three-layer hollow nano-silica was dissolved in 75g of mixed solvent, and magnetically stirred at 400rpm for 10min. After being uniform, 1.25g of wetting dispersant (purchased from BYK Chemical DISPERBYK-2026) was added and stirred at 500rpm for 20min to obtain a uniformly mixed suspension of hollow silica. The speed was reduced to 200rpm, and the above-mentioned uniformly stirred resin system was slowly added to the stirring suspension of hollow silica. The magnetic stirring speed was increased to 500rpm, and stirring was continued for 30min to obtain a low-reflection coating liquid. Finally, the speed was adjusted to 200rpm, and the surface was defoamed after low-speed stirring before use.
[0220] The steps for preparing the three-layer structure of hollow nano-silica are as described in Example 7. The coating method and curing method are as described in Example 7 to obtain the anti-glare, anti-reflection and anti-fingerprint film.
[0221] Example 10
[0222] PANDEX P-910: 0.87g
[0223] Sapience SPC-1410: 4.33g
[0224] Irgacure TPO: 0.16g
[0225] BasonatHI100ap: 0.15g
[0226] STA-3306: 0.35g
[0227] Modified hollow silica: 1.56g
[0228] BYK DISPERBYK-170TF: 0.5g
[0229] Mixed solvent: 92.08g
[0230] Pour 0.87 g of polyurethane (DIC Corporation PANDEX P-910), 4.33 g of silicon-modified polyurethane acrylate resin low-fold resin (sapience SPC-1410), 0.16 g of photoinitiator (BASF Irgacure TPO), 0.15 g of thermal curing agent (BASF Basonat HI100ap), 0.35 g of silicone leveling agent (STA-3306) and 54.58 g of a mixed solvent of ethyl acetate and methyl isobutyl ketone in a mass ratio of 1:1 into a beaker, and stir at a low speed of 300 rpm for 10 minutes to mix the resin system evenly.
[0231] 1.2g of the prepared three-layer hollow nano-silica was dissolved in 37.5g of the mixed solvent, and magnetically stirred at 400rpm for 10min. After being uniform, 0.5g of wetting dispersant (purchased from BYK DISPERBYK-170TF) was added, and then stirred at 500rpm for 20min to obtain a uniformly mixed suspension of hollow silica. The speed was reduced to 200rpm, and the above-mentioned uniformly stirred resin system was slowly added to the stirring suspension of hollow silica, and the magnetic stirring speed was increased to 500rpm, and stirring was continued for 30min to obtain a low-reflection coating liquid. Finally, the speed was adjusted to 200rpm, and the surface was defoamed after stirring at a low speed before use.
[0232] The steps for preparing the three-layer structure of hollow nano-silica are as described in Example 7. The coating method and curing method are as described in Example 7 to obtain the anti-glare, anti-reflection and anti-fingerprint film.
[0233] Embodiment 11
[0234] PANDEX P-910: 0.47g
[0235] Sapience SPC-1410: 4.73g
[0236] Irgacure TPO: 0.16g
[0237] BasonatHI100ap: 0.15g
[0238] STA-3306: 0.35g
[0239] Modified hollow silica: 1.56g
[0240] BYK DISPERBYK-170TF: 0.5g
[0241] Mixed solvent: 92.08g
[0242] Pour 0.47g of polyurethane (DIC Corporation PANDEX P-910), 4.73g of silicon-modified polyurethane acrylate resin low-fold resin (sapience SPC-1410), 0.16g of photoinitiator (BASF Irgacure TPO), 0.15g of thermal curing agent (BASF Basonat HI100ap), 0.35g of silicone leveling agent (STA-3306) and 54.58g of a mixed solvent of ethyl acetate and methyl isobutyl ketone in a mass ratio of 1:1 into a beaker, and stir at a low speed of 300 rpm for 10 minutes to mix the resin system evenly.
[0243] 1.56g of the prepared three-layer hollow nano-silica was dissolved in 37.5g of the mixed solvent, and magnetically stirred at 400rpm for 10min. After being uniform, 0.5g of wetting dispersant (purchased from BYK DISPERBYK-170TF) was added, and then stirred at 500rpm for 20min to obtain a uniformly mixed suspension of hollow silica. The speed was reduced to 200rpm, and the above-mentioned uniformly stirred resin system was slowly added to the stirring suspension of hollow silica, and the magnetic stirring speed was increased to 500rpm, and stirring was continued for 30min to obtain a low-reflection coating liquid. Finally, the speed was adjusted to 200rpm, and the surface was defoamed after stirring at a low speed before use.
[0244] The steps for preparing the three-layer structure of hollow nano-silica are as described in Example 7. The coating method and curing method are as described in Example 7 to obtain the anti-glare, anti-reflection and anti-fingerprint film.
[0245] Comparative Example 4
[0246] PANDEX P-910: 0g
[0247] SPC-1410: 5.2g
[0248] Irgacure TPO: 0.16g
[0249] BasonatHI100ap: 0.15g
[0250] STA-3306: 0.35g
[0251] Modified hollow silica: 1.56g
[0252] BYK DISPERBYK-170TF: 0.5g
[0253] Mixed solvent: 92.08g;
[0254] Pour 5.2g of silicon-modified polyurethane acrylate low-fold resin (sapience SPC-1410), 0.16g of photoinitiator (BASF Irgacure TPO), 0.15g of thermal curing agent (BASF Basonat HI100ap), 0.35g of silicone leveling agent (STA-3306) and 54.58g of a mixed solvent of ethyl acetate and methyl isobutyl ketone in a mass ratio of 1:1 into a beaker, and stir at a low speed of 300 rpm for 10 minutes to mix the resin system evenly.
[0255] 1.2g of the prepared three-layer hollow nano-silica was dissolved in 37.5g of the mixed solvent, and magnetically stirred at 400rpm for 10min. After being uniform, 0.5g of wetting dispersant (purchased from BYK DISPERBYK-170TF) was added, and then stirred at 500rpm for 20min to obtain a uniformly mixed suspension of hollow silica. The speed was reduced to 200rpm, and the above-mentioned uniformly stirred resin system was slowly added to the stirring suspension of hollow silica, and the magnetic stirring speed was increased to 500rpm, and stirring was continued for 30min to obtain a low-reflection coating liquid. Finally, the speed was adjusted to 200rpm, and the surface was defoamed after stirring at a low speed before use.
[0256] The steps for preparing the three-layer structure of hollow nano-silica are as described in Example 7. The coating method and curing method are as described in Example 7 to obtain the anti-glare, anti-reflection and anti-fingerprint film.
[0257] Comparative Example 5
[0258] PANDEX P-910: 1.5g
[0259] Sapience SPC-1410: 3.7g
[0260] Irgacure TPO: 0.16g
[0261] BasonatHI100ap: 0.15g
[0262] STA-3306: 0.35g
[0263] Modified hollow silica: 1.56g
[0264] BYK DISPERBYK-170TF: 0.5g
[0265] Mixed solvent: 92.08g;
[0266] Pour 1.5 g of polyurethane (DIC Corporation PANDEX P-910), 3.7 g of silicon-modified polyurethane acrylate resin low-fold resin (sapience SPC-1410), 0.16 g of photoinitiator (BASF Irgacure TPO), 0.15 g of thermal curing agent (BASF Basonat HI100ap), 0.35 g of silicone leveling agent (STA-3306) and 54.58 g of a mixed solvent of ethyl acetate and methyl isobutyl ketone in a mass ratio of 1:1 into a beaker, and stir at a low speed of 300 rpm for 10 minutes to mix the resin system evenly.
[0267] 1.56g of the prepared three-layer hollow nano-silica was dissolved in 37.5g of the mixed solvent, and magnetically stirred at 400rpm for 10min. After being uniform, 0.5g of wetting dispersant (purchased from BYK DISPERBYK-170TF) was added, and then stirred at 500rpm for 20min to obtain a uniformly mixed suspension of hollow silica. The speed was reduced to 200rpm, and the above-mentioned uniformly stirred resin system was slowly added to the stirring suspension of hollow silica, and the magnetic stirring speed was increased to 500rpm, and stirring was continued for 30min to obtain a low-reflection coating liquid. Finally, the speed was adjusted to 200rpm, and the surface was defoamed after stirring at a low speed before use.
[0268] The steps for preparing the three-layer structure of hollow nano-silica are as described in Example 7. The coating method and curing method are as described in Example 7 to obtain the anti-glare, anti-reflection and anti-fingerprint film.
[0269] Table 2. Anti-glare, anti-reflection and anti-fingerprint film performance test results
[0270]
[0271]
[0272] Table 3. Test data after anti-glare, anti-reflection and anti-fingerprint film wear test (500g-300 times)
[0273]
[0274] Table 4. Test data after abrasion resistance (500g-1000 times) test
[0275]
[0276] Based on the test results of various physical properties of the anti-glare, anti-reflection and anti-fingerprint film, it can be learned that the ratio of resin 2 and resin 3, the ratio of modified hollow silica, etc. have a great influence on the adhesion, reflectivity and other properties of the anti-glare, anti-reflection and anti-fingerprint film. For example, in Example 11, the ratio of thermosetting resin and modified hollow silica is appropriate, and its adhesion, reflectivity and stability are excellent. On the other hand, in Comparative Example 3, the ratio of thermosetting resin is 0%, the adhesion is poor, the reflectivity stability is also poor, and it quickly weakens with the wear resistance test.
[0277] The test methods for each performance in the table are as follows:
[0278] (1) Haze / light transmittance
[0279] The haze transmittance was tested using a haze meter (Nippon Denshoku Co., Ltd.; model NDH2000N).
[0280] (2) Water contact angle
[0281] With reference to the standard GB / T 30693-2014, the water contact angle was measured using the SL150E contact angle analyzer produced by American Kono Industries Co., Ltd.
[0282] (3) Roughness
[0283] According to the standard GBT1031-2009, a roughness meter (Mitutoyo, Japan; model SJ210) was used to test the surface roughness of the film-forming product.
[0284] (4) Coating adhesion
[0285] Referring to the standard GB / T 9286, the hard coating surface of the hard coating film was cut into 100 cross-section lines with a cutter, wherein the size of each cross-section line was 1 mm×1 mm, and then 3M-610 professional test tape (3M Company) was adhered to the cross-section hard coating surface with a force of 2.0 kg. After 3 minutes, the 3M tape was peeled off from the surface at an angle of 180°. The coating adhesion was evaluated by counting the number of cross-section lines of the hard coating remaining on the support, and was divided into 5 levels from low to high, namely 1B, 2B, 3B, 4B and 5B.
[0286] (5) Reflectivity
[0287] Referring to GB / T 27583-2011, a spectrophotometer (KONICA MINOLTA; model: CM-5) was used to test the full spectrum reflectance of visible light on the surface of the film-forming product.
[0288] (6) Internal and external haze test
[0289] The test was performed using a haze meter (Nippon Denshoku Co., Ltd.; model NDH2000N) with reference to the method described in the patent "Structure for Convenient Testing of Haze" (Publication No.: CN218767384U).
[0290] (7) Wear-resistant coating
[0291] Referring to the HG / T 4303 test standard, the wear resistance testing machine (Jingjia Instrument Equipment Co., Ltd., model: A20-339) was used to test the friction resistance of the film-forming product.
Claims
1. An anti-glare, anti-reflection, and anti-fingerprint film, comprising a transparent support, an anti-glare hardening coating, and an anti-reflection coating; characterized in that: The anti-glare hardened coating is obtained by coating and curing a coating solution made of the following components in parts by mass: Resin 1: 20-40 parts Resin 2: 1.8-4.8 parts Photoinitiator: 0.75-3.25 parts Thermal curing agent: 0.3-1.75 parts Anti-glare particles: 0.75-4.75 parts Leveling agent 1: 0.25-1.25 parts Leveling agent 2: 0.03-0.15 parts Solvent: 44.05-76.12 parts; The anti-reflection coating is formed by coating and curing a coating solution made of the following components in parts by mass: Resin 2: 0.47-1.8 parts Resin 3: 2.4-6.0 parts Photoinitiator: 0.12-0.75 parts Thermal curing agent: 0.1-0.45 parts Leveling agent 3: 0.18-1.65 parts Modified hollow silica: 0.56-2.4 parts Wetting and dispersing agent: 0.1-1.25 parts Solvent: 85.7-95.74 parts; The modified hollow silica is a three-layer structured hollow silica nanoparticle formed by compounding polydimethylsiloxane (PDMS) on the surface of the hollow silica nanoparticle and then surface-modifying the hollow silica nanoparticle with 3-glycidyloxypropyltrimethoxysilane (GPTMS).
2. The anti-glare, anti-reflection and anti-fingerprint film according to claim 1, characterized in that: The anti-glare particles contained in the anti-glare hardening coating are monodisperse particles, and their particle size D1 and the thickness H1 of the anti-glare hardening coating satisfy the following relationship: H1≤D1≤5 / 4H1, 1.5um≤H1≤4um; the particle size D2 of the modified hollow silica nanoparticles and the thickness H2 of the anti-reflection coating satisfy: 90nm≤H2≤150nm, D2<90nm.
3. The anti-glare, anti-reflection and anti-fingerprint film according to claim 1, characterized in that: The anti-glare hardening coating comprises resin 1 and resin 2; the resin 1 is polyurethane acrylic resin, the curing method is UV energy curing, the functionality is 6-9, and the molecular weight is 1000-8000; the resin 2 is polyol acrylate, the curing method is thermal cross-linking curing, the hydroxyl value is 85-120, the thermal curing conditions are 80-100°C, 5-10min, and the curing temperature is 60°C for ≥12h; The mass of the resin 2 in the anti-glare hardened coating is not higher than 12% of the mass of the resin 1.
4. The anti-glare, anti-reflection and anti-fingerprint film according to claim 1, characterized in that: The anti-reflection coating uses resin 2 and resin 3; The resin 3 is a low-refractive modified polyurethane acrylic resin, which is cured by UV energy and has a refractive index of 1.35±0.1; The mass of resin 2 in the anti-reflection coating is not higher than 30% of the mass of resin 3.
5. The anti-glare, anti-reflection and anti-fingerprint film according to claim 1, characterized in that: The leveling agent 1 is an acrylic leveling agent, and the leveling agents 2 and 3 are silicone leveling agents.
6. The anti-glare, anti-reflection and anti-fingerprint film according to claim 1, characterized in that: The solvent used in the anti-glare hardening coating liquid is a mixed solvent of n-propanol, butyl acetate and butanone, and the mixed solubility parameter of the mixed solvent is 9 to 11; The solvent used in the anti-reflection coating liquid is a mixed solvent of ethyl acetate and methyl isobutyl ketone, and the mixed solubility parameter of the mixed solvent is 7-10.
7. The anti-glare, anti-reflection and anti-fingerprint film according to claim 1, characterized in that: The transparent support is one of TAC, PET, SRF, PMMA or PI.
8. The anti-glare, anti-reflection and anti-fingerprint film according to claim 1, characterized in that: The transparent support has a thickness of 40-125 μm.
Citation Information
Patent Citations
Structure convenient for testing haze
CN218767384U
Cited By
Anti-fingerprint ceramic, manufacturing method of anti-fingerprint ceramic, switch panel and manufacturing method of switch panel
CN121362043A